2022
DOI: 10.3390/nu14194014
|View full text |Cite
|
Sign up to set email alerts
|

Association of Body Mass Index with Risk of Household Catastrophic Health Expenditure in China: A Population-Based Cohort Study

Abstract: Catastrophic health expenditure (CHE) is a major obstacle to achieving universal health coverage, and body mass index (BMI) is linked to both health and economy. We aimed to explore the association of BMI with the risk of CHE to provide advice for reducing CHE. We used national cohort data from the China Family Panel Studies, which comprised 33,598 individuals (14,607 households) from 25 provinces between 2010 to 2018. We used multivariate Cox proportional hazard models to estimate adjusted hazard ratios (aHRs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 38 publications
(44 reference statements)
0
5
0
Order By: Relevance
“…Thus, it is recommended that policies be implemented in favour of these cancer types, which impose heavier burdens on patients compared with others. In addition, it is necessary to integrate medical assistance policies that focus on helping low-income impoverished groups and improving the expenditure target identification mechanism to prevent patients from falling into poverty or returning to poverty due to their illness [44].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is recommended that policies be implemented in favour of these cancer types, which impose heavier burdens on patients compared with others. In addition, it is necessary to integrate medical assistance policies that focus on helping low-income impoverished groups and improving the expenditure target identification mechanism to prevent patients from falling into poverty or returning to poverty due to their illness [44].…”
Section: Discussionmentioning
confidence: 99%
“…A study from Bangladesh also concluded that people from lower income quintiles have lower CHE as the utilization of formal care is low [31]. Conversely, poverty consistently predicts CHE, indicating that poor people have higher CHE [13,18,21,27,28,37,46,48,54,58]. To safeguard poor people from financial catastrophe, several studies from China, Kenya, and Malaysia emphasized on health insurance [19,20,36,54].…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, poverty consistently predicts CHE, indicating that poor people have higher CHE [13,18,21,27,28,37,46,48,54,58]. To safeguard poor people from financial catastrophe, several studies from China, Kenya, and Malaysia emphasized on health insurance [19,20,36,54]. However, countries where health insurance is available reported that due to insufficient coverage and the delay in reimbursement, health insurance could not save people from CHE [43].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations